2015
DOI: 10.3906/elk-1212-50
|View full text |Cite
|
Sign up to set email alerts
|

DWMT transceiver equalization using overlap FDE for downlink ADSL

Abstract: Discrete wavelet multitone (DWMT) modulation is a wavelet transform based technique implemented using perfect reconstruction filter banks. It has been recently proposed for various wireline channels such as digital subscriber loops (DSLs) as a solution to the problems posed by a discrete multitone (DMT) transceiver including interblock interference (IBI) and lower spectral efficiency due to the employment of a cyclic prefix (CP) in the guard interval (GI) for DMT symbols. The greater side lobe attenuation offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…For the first time, Overlap FDE was applied by Tomeba for MCM systems [13] and later used by Sohaib for wavelet OFDM [13]. In [7], authors showed its supremacy for ADSL systems for DWMT transceiver in presence of AWGN and FEXT, NEXT. In this paper, we are evaluating Overlap FDE performance for ADSL systems for DWMT transceiver in presence of AWGN, FEXT, NEXT and impulse noise.…”
Section: B Overlap Frequency Domain Equalizationmentioning
confidence: 99%
See 4 more Smart Citations
“…For the first time, Overlap FDE was applied by Tomeba for MCM systems [13] and later used by Sohaib for wavelet OFDM [13]. In [7], authors showed its supremacy for ADSL systems for DWMT transceiver in presence of AWGN and FEXT, NEXT. In this paper, we are evaluating Overlap FDE performance for ADSL systems for DWMT transceiver in presence of AWGN, FEXT, NEXT and impulse noise.…”
Section: B Overlap Frequency Domain Equalizationmentioning
confidence: 99%
“…Here is dimension of the signal. For Overlap FDE, the complexity of points is given by, [ ( ( )) ] represents the size of IFFT/FFT [7]. Complexity comparison for TDE and Overlap FDE for DWMT transceiver is shown in Table III. VII.…”
Section: Computational Complexity Comparisonmentioning
confidence: 99%
See 3 more Smart Citations